A political history of the Arameans : from their origins to the end of their polities - Younger, K. Lawson, Jr (Archaeology and biblical studies, 2016)
"K. Lawson Younger Jr. presents a political history of the Arameans from their earliest origins to the demise of their independent entities. The book investigates their tribal structures, the development of their polities, and their interactions with other groups in the ancient Near East. Younger utilizes all of the available sources to develop a comprehensive picture of this complex, yet highly important, people whose influence and presence spanned the Fertile Cresent"--